RECENT TRENDS CONCERNING THE DEVELOPMENT OF INTERNATIONAL TOURISM - Butnaru, Gina Ionela; Anichiti, Alexandru; Păvăluc (Melinte), Cristiana (Revista de turism - studii și cercetări în turism, 2020)
Tourism is one of the largest economic sectors in the world. The rapid development of international tourism arises from the diversifcation of tourist services, modernisation of the means of transportation, easier international travel and the increase of disposable income for tourists in emerging countries. This research offers a quantitative analysis regarding the current state of tourism with its trends and challenges. The study includes statistics from World Tourism Organization and Eurostat regarding the recent developments in the tourism sector. These statistics can help explain the forces that have driven the tourism sector to become such a major contributor to the world economy and what forces will drive it going forward.